2018
DOI: 10.1103/physrevb.98.104305
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order spacing ratios in random matrix theory and complex quantum systems

Abstract: The distribution of the ratios of nearest neighbor level spacings has become a popular indicator of spectral fluctuations in complex quantum systems such as the localized and thermal phases of interacting many-body systems, quantum chaotic systems, and in atomic and nuclear physics. In contrast to the level spacing distribution, which requires the cumbersome and at times ambiguous unfolding procedure, the ratios of spacings do not require unfolding and are easier to compute. In this work, for the class of Wign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 56 publications
9
37
0
Order By: Relevance
“…4 can be expected to be independent of T /N . Similar scaling relation had been postulated for the spacing distribution of Gaussian ensembles [34] and its generalizations [35], and recently numerical evidence was provided for the ratios [36]. Both P k (r, β) and P (r, β ′ ) have identical functional forms and the modified parameter β ′ depends on the order k of the spacing ratio and co-dimension β.…”
Section: Distribution Of Higher Order Spacing Ratiossupporting
confidence: 64%
See 1 more Smart Citation
“…4 can be expected to be independent of T /N . Similar scaling relation had been postulated for the spacing distribution of Gaussian ensembles [34] and its generalizations [35], and recently numerical evidence was provided for the ratios [36]. Both P k (r, β) and P (r, β ′ ) have identical functional forms and the modified parameter β ′ depends on the order k of the spacing ratio and co-dimension β.…”
Section: Distribution Of Higher Order Spacing Ratiossupporting
confidence: 64%
“…This finite size or convergence effect has also been discussed for Gaussian ensembles in Ref. [36]. While in the bottom panel, it is observed that the minima of D(β ′ ) does not converge to the predicted value β ′ = 229 even on considering a (relatively) small range of eigenvalues in the bulk.…”
Section: B Stock Market and Atmospheric Datasupporting
confidence: 60%
“…Evidence for a broader class of interrelations involving β = 1, 2, 4 has been provided recently in Ref. [42]. Fig.…”
mentioning
confidence: 75%
“…A straight-forward generalization, left for future work, would be to consider the statistics of the ratios s kCN i /s (k+1)CN i , which would give insight into longer range correlations. It is noteworthy that a recent work [55] explores certain higher range spacing ratios of a kind that is not based on ordering.…”
Section: Summary and Discussionmentioning
confidence: 99%